Effect of Digital Health on Mobilization in Post-Operative Fracture Patients: A Systematic Review - Baiq Rista Ananta Pratiwi; Ninuk Dian Kurniawati; Ika Nur Pratiwi (Indonesian Journal of Global Health Research, 2025)
Post-operative rehabilitation for fracture patients is crucial in restoring mobility and preventing complications such as muscle atrophy, joint stiffness, and deep vein thrombosis. However, traditional rehabilitation methods often face significant barriers, including limited accessibility, high costs, and low patient adherence. These challenges highlight the need for innovative approaches to enhance rehabilitation outcomes. Digital health interventions (DHIs), such as mobile applications, telerehabilitation, and IoT (Internet of Things) devices, have emerged as promising solutions. By providing remote monitoring, real-time feedback, and personalized care, DHIs address many of the limitations of traditional rehabilitation methods and offer opportunities to improve recovery outcomes. Objective: This systematic review aims to evaluate the effectiveness of digital health interventions (DHIs) in improving mobilization and overall recovery for post-operative fracture patients. Methods: A comprehensive search was conducted across PubMed, Scopus, ScienceDirect, Web of Science, and ProQuest for studies published between 2019 and 2024. Keywords included "digital health," "mobilization," "post-operative fractures," and "telerehabilitation." The review included randomized controlled trials (RCTs), cohort studies, and systematic reviews that evaluated DHIs for post-operative fracture rehabilitation. The inclusion criteria were studies involving post-operative fracture patients, DHIs (e.g., mobile apps, telerehabilitation, IoT devices), and outcomes related to mobility, pain management, and patient satisfaction. The quality of studies was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool. Results: A total of 10 studies were included, involving 1,200 post-operative fracture patients. These studies assessed various digital health interventions, including mobile applications, IoT-based devices, and telerehabilitation. The results indicated significant improvements in mobilization, pain reduction, and patient satisfaction. Patients in the DHI groups demonstrated faster recovery times, better adherence to rehabilitation programs, and improved overall functional outcomes compared to traditional rehabilitation methods. Conclusions: Digital health interventions significantly improve mobilization and recovery outcomes for post-operative fracture patients. These interventions provide accessible, cost-effective, and personalized rehabilitation solutions. DHIs offer a valuable complement to traditional rehabilitation methods and have the potential to enhance patient care and satisfaction. Future research should focus on optimizing the implementation of these technologies and assessing long-term outcomes.